Professional identity development among graduate students during the field practicum - Shands-Baab, Connie (ProQuest Dissertations & Theses, 2008)
The purpose of this study was to explore how field practicum instructors understand the identity development of master's of social work (MSW) students during field practicum. Two primary research questions guided the study. The first was, How do field instructors define professional identity development? The second was, What do they believe about the process of this development during the field practicum? A qualitative phenomenological method, which used a narrative approach, was selected to elicit the meanings, interpretations, and experiences of the field practicum instructors in the rich language that they used to describe their understanding of identity development among MSW students during the field practicum. The subjects were selected using a purposive sample technique to identify 11 unique participants who provided diversity in terms of age, years of experience as a social worker, type of setting where the subject has performed field instruction, and area of practice. Semistructured interviews were conducted as a way of gathering the data for this study. The first two interviews were treated as pilot interviews to evaluate the questionnaire. Initial and follow-up interviews were then conducted. Coding resulted in five universal themes. Those themes were as follows: (a) motivation to provide field instruction, (b) impacts on the field instructors' ability to provide field instruction, (c) the role of field practicum, (d) field instructors' perspectives of process, and (e) field instructors' reflections on their own field practicums. The ecosystems perspective and the socialization of field instructors are discussed to provide a context for the themes. The object relations theories of Winnicott and Mahler are also discussed as tools for understanding the developmental processes. Erikson's developmental theory is also discussed as it relates to this study. The findings indicate that none of these theories correspond exactly to the participants' narratives or the identified themes. Recommendations for further study are made. They include the following: (a) exploring how identified themes in field instructors' narratives might be used as source data for a formal theory of professional identity development, (b) evaluating the influence of the sociopolitical environment on the socialization process, and (c) understanding the contributions that training for field instructors makes to the formation of professional identity development.